Eco-friendly highly efficient BN/rGO/TiO2 nanocomposite visible-light photocatalyst for phenol mineralization - Shekhah Al-Kandari (14151720) (2022)
Boron nitride (BN) and reduced graphene oxide (rGO) of different loadings were composited with commercial P25 TiO2 (Ti) through the hydrothermal method. The as-prepared nanocomposites were characterized using various techniques: X-ray photoelectron spectroscopy, X-ray diffraction, thermal gravimetric analysis, Fourier transform infrared and Raman spectroscopies, and transmission and scanning electron microscopies. It was observed that 10% and 0.1% of BN and rGO, respectively, loaded on TiO2 (10BNr0.1GOTi) resulted in the best nanocomposite in terms of phenol degradation under simulated sunlight. A 93.4% degradation of phenol was obtained within 30 min in the presence of H2O2. Finally, to ensure the safe use of BNrGOTi nanoparticles in the aquatic environment, acute zebrafish toxicity (acutoxicity) assays were studied. The 96-h acute toxicity assays using the zebrafish embryo model revealed that the LC50 for the BNrGOTi nanoparticle was 677.8 mg L−1 and the no observed effect concentration (NOEC) was 150 mg L−1. Therefore, based on the LC50 value and according to the Fish and Wildlife Service Acute Toxicity Rating Scale, BNrGOTi is categorized as a “practically not toxic” photocatalyst for water treatment. Other Information Published in: Environmental Science and Pollution Research License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: http://dx.doi.org/10.1007/s11356-021-15083-y